2020
DOI: 10.26719/emhj.20.009
|View full text |Cite
|
Sign up to set email alerts
|

Patient reluctance to accept Do Not Resuscitate order: impact on clinical care

Abstract: Background: A Do Not Resuscitate (DNR) order should only impede the performance of cardiopulmonary resuscitation in case of cardiac or respiratory arrest; it should not interfere with any other treatment decisions. Aims: To study the impact of DNR order placement on daily clinical care of patients. Methods: This was a retrospective cohort study of 72 patients in a tertiary care centre in Saudi Arabia. Daily clinical care measures were collected for 2 weeks prior and 2 weeks after DNR order placement and includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Still, it required deeper knowledge to learn whether there is a clear local or national DNR policy. Those who knew about the policy did not read in detail [ 60 63 , 67 , 68 , 70 ]. The most common limitation of essential discussions about DNR was a lack of patient understanding, educational level, cultural background of patients, and a lack of DNR policy knowledge by medical staff [ 60 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Still, it required deeper knowledge to learn whether there is a clear local or national DNR policy. Those who knew about the policy did not read in detail [ 60 63 , 67 , 68 , 70 ]. The most common limitation of essential discussions about DNR was a lack of patient understanding, educational level, cultural background of patients, and a lack of DNR policy knowledge by medical staff [ 60 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which patients were included as a target population reported a lack of knowledge of the medical conditions for DNR practice [ 62 , 65 , 66 , 68 , 69 ]. Patients expressed a will to participate in discussions with doctors on planning end-of-life care and making their own decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some patients wish not to be resuscitated. The literature has studied this order, the Do-Not-Resuscitate (DNR), for patients who suffer from severe burns, 3 cardiopulmonary insufficiency, 4 cancer, 5 dementia, 6 and for the elderly. 7 As of 2008, CPR has been implemented under the code blue procedure, and the right of DNR has been contested.…”
Section: Introductionmentioning
confidence: 99%